Expression of Th17/Treg Cells in Peripheral Blood and Related Cytokines of Patients with Ulcerative Colitis of Different Syndrome Types and Correlation with the Disease. (24th September 2021) - Yu, Jianhua; Wang, Shu; Yuan, Hongsheng; Qiao, Tingyue; Bao, Miao
Abstract : Objective . To explore the expression of helper T cells 17 (Th17)/regulatory T cells (Treg) in peripheral blood and related cytokines of patients with different types of ulcerative colitis (UC) and analyze their correlation with the disease. Methods . From January 2018 to December 2019, 53 patients diagnosed with UC in our hospital were selected. According to their medical syndromes, they were divided into the damp-heat internal accumulation group ( n  = 35) and the spleen-kidney yang deficiency group ( n  = 18). 21 healthy volunteers were selected as the control group. The Mayo scoring standard was used to determine the severity of the patient's condition. The expression levels of Th17/Treg cells and related cytokines in peripheral blood were compared between the groups. Pearson correlation was used to analyze the correlation between the ratio of Th17 and Treg cells in the peripheral blood of UC patients and the ratio of TH17/Treg with Mayo score. Results . The peripheral blood Th17 cell ratio and Th17/Treg ratio of the damp-heat internal accumulation and spleen-kidney yang deficiency group were higher than those of the control group; the Treg cell ratio was lower than that of the control group; the peripheral blood Th17 cell ratio and Th17/Treg ratio of the damp-heat internal accumulation group were higher those of the spleen-kidney yang deficiency group; and the proportion of Treg cells was lower than that of the spleen-kidney yang deficiency group (P < 0.05 ). The expression levels of serum IL-6, IL-17, IL-22, and TNF- α in the damp-heat internal accumulation and spleen-kidney yang deficiency group were higher than those of the control group; IL-10 and TGF- β were lower than those of the control group; the levels of serum IL-6, IL-17, IL-22, and TNF- α in the damp-heat internal accumulation group were higher than those of the spleen-kidney yang deficiency group; and both IL-10 and TGF- β were lower than those of the spleen-kidney yang deficiency group (P < 0.05 ). The peripheral blood Th17 cell ratio and Th17/Treg ratio in the moderately active period group and severely active period group were higher than those of the lightly active period group; the Treg cell ratio was lower than that of the lightly active period group; the peripheral blood Th17 cell ratio and Th17/Treg ratio in the severely active period group were higher than those in the moderately active period group; and the proportion of Treg cells was lower than that of the moderately active period group. Pearson correlation analysis showed that the proportion of Th17 cells and Th17/Treg in peripheral blood of UC patients were both positively correlated with Mayo score ( r  = 0.762, r  = 0.777, P < 0.001 ). Treg was negatively correlated with Mayo score ( r  = −0.790, P < 0.001 ). Conclusion . There are differences in the expression of peripheral blood Th17/Treg cells and related cytokines among UC patients with different syndromes, and the damp-heat content is the most significant. The higher the ratio of Th17 cells in peripheral blood and the degree of Th17/Treg imbalance, the lower the ratio of Treg cells, and the more severe the condition of UC patients, which can provide a preliminary quantitative basis for the TCM classification and severity of the diagnosis of UC.